Delivery Delays from International Suppliers: Management Practises and Associated Costs : A case study in Strategic Purchasing - Rautiainen, Ella (My University, 2026)
The concept of Global sourcing has become an increasingly important strategic approach for organizations seeking cost efficiency, access to specialized supplier capabilities and broader supply markets. However, the increasing complexity of global supply chains has increased organizations’ exposure to delivery-related disruptions and operational uncertainty as well. De-livery delays from international suppliers may create operational and cost implications throughout the procurement and production processes, highlighting the effective delay management and supply chain resilience. The objective of this study is to examine how organizations manage delivery delays from international suppliers and to analyse the associated operational and cost implications. The study was conducted as a qualitative single case study within the procurement organization of a Finnish multinational company operating in the marine industry. Empirical data was collected through semi-structured interviews with nine participants representing operational purchasing, strategic purchasing, supplier development and category management roles. The findings indicate that delivery delays emerge through a combination of supplier-related factors, internal planning instability and the complexity of global supply chains. Organizations manage delays primarily through reactive operational practices aimed at maintaining production continuity, while proactive strategies were identified as important mechanism for improving long-term resilience and delivery reliability. The results further demonstrate that delivery delays generate significant operational consequences extending beyond transportation or logistics-related disruptions. In addition, delays create substantial indirect and hidden costs through coordination activities, expedited deliveries, alternative sourcing arrangements and production-related adjustments. Despite these implications, production continuity was frequently prioritized over cost efficiency, making the full financial impact of delivery disruptions difficult to identify and evaluate systematically. The study highlights the importance of improving supplier visibility, strengthening proactive supplier management practices and adopting broader perspective on disruption-related costs in global sourcing environments.

Kansainvälisestä hankinnasta on tullut yhä keskeisempi strateginen lähestymistapa organisaatioille, jotka tavoittelevat kustannustehokkuutta, pääsyä erikoistuneiden toimittajien osaamiseen sekä laajempia hankintamarkkinoita. Samanaikaisesti globaalien toimitusketjujen kasvava monimutkaisuus on lisännyt organisaatioiden altistumista toimitushäiriöille ja operatiiviselle epävarmuudelle. Kansainvälisten toimittajien toimitusviiveet voivat aiheuttaa merkittäviä vaikutuksia hankinta- ja tuotantoprosesseihin, mikä korostaa tehokkuuden sekä toimitusketjujen resilienssin merkitystä. Tämän tutkimuksen tavoitteena on tarkastella, miten organisaatiot hallitsevat kansainvälisten toimittajien toimitusviiveitä sekä analysoida viiveiden aiheuttamia operatiivisia ja taloudellisia vaikutuksia. Tutkimus toteutettiin laadullisena tapaustutkimuksena suomalaisen meriteollisuudessa toimivan monikansallisen yrityksen hankintaorganisaatiossa. Empiirinen aineisto kerättiin puolistrukturoitujen haastattelujen avulla. Tutkimustulokset osoittavat, että toimitusviiveet syntyvät useiden tekijöiden yhteisvaikutuksesta, johon kuuluvat toimittajiin liittyvät haasteet, sisäisen suunnittelun epävakaus sekä globaalien toimitusketjujen monimutkaisuus. Organisaatiot hallitsevat viiveitä ensisijaisesti reaktiivisten toimintatapojen avulla tuotannon jatkuvuuden turvaamiseksi, kun taas ennakoivien strategioiden havaittiin olevan keskeisessä roolissa pitkän aikavälin toimitusvarmuuden ja toimitusketjujen resilienssin vahvistamisessa. Viiveet aiheuttavat merkittäviä epäsuoria ja piileviä kustannuksia muun muassa koordinointityön lisääntymisen, kiireellisten toimitusjärjestelyjen, vaihtoehtoisten hankintaratkaisujen sekä tuotannon sopeuttamistoimenpiteiden kautta. Näistä vaikutuksista huolimatta tuotannon jatkuvuuden varmistaminen asetettiin usein kustannustehokkuuden edelle, mikä vaikeuttaa toimitushäiriöiden kokonaisvaltaisten taloudellisten vaikutusten tunnistamista ja systemaattista arviointia. Tutkimus korostaa toimittajanäkyvyyden kehittämisen, ennakoivan toimittajahallinnan vahvistamisen sekä toimitushäiriöihin liittyvien kustannusten laajemman tarkastelun merkitystä globaaleissa hankintaympäristöissä.
Keywords: supply chains; costs; suppliers; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business